Bali Included as ‘No List 2020’, a Shocking news on the end of 2019 - Ida Bagus Putra Setiawan (Bali Tourism Board, 2019)
A US-based tourism magazine ‘Fodor’ includes Bali as ‘No List 2020’. The news infuriated Bali Governor Wayan Koster. Koster presumed the action was an example of foul play in tourism competition. Meanwhile, Minister of Tourism and Creative Economy, Wishnutama Kusbandio claimed he did not bother with the Fodor's review. The news might be the Fodor’s strategy as a media to reach a wider audience. Fodor’s included Bali as